Combined effect of pressure and temperature for yogurt production. (August 2019) - Lopes, Rita P.; Mota, Maria J.; Sousa, Sérgio; Gomes, Ana M.; Delgadillo, Ivonne; Saraiva, Jorge A.
Abstract: Fermentation under non-conventional conditions has gained prominence in the last years, due to the possible process improvements. Fermentation under sub-lethal pressures is one of such cases, and may bring novel characteristics and features to fermentative processes and products. In this work, the effect of both pressure (10–100 MPa) and temperature (25–50 °C) on yogurt production fermentation kinetics was studied, as a case-study. Product formation and substrate consumption were evaluated over fermentation time and the profiles were highly dependent on the fermentation conditions used. For instance, the increase of pressure slowed down yogurt fermentation, but fermentative profiles similar to atmospheric pressure (0.1 MPa) were obtained at 10 MPa at almost all temperatures tested. Regarding temperature, higher fermentative rates were achieved at 43 °C for all pressures tested. Moreover, the inhibitory effect of pressure increased when temperature decreased, with complete inhibition of fermentation occurring at 50 MPa for 25–35 °C, contrasting to 43 °C where inhibition occurred only at 100 MPa. Therefore, an antagonistic effect seems to occur, since yogurt fermentation was slowed down by pressure increasing, on one hand, and by temperature decreasing, on the other hand. Additionally, some kinetic parameters were calculated and fermentation at 43 °C presented the best results for yogurt production, with lower fermentation times and higher lactic acid productivities. Interestingly, fermentation at 10 MPa/43 °C presented the optimal conditions, with improved yield and lactic acid production efficiency, when compared to fermentation at 0.1 MPa (efficiency of 75% at 10 MPa, against 40% at 0.1 MPa). As the authors are aware, this work gives the first insights about the simultaneous effect of pressure and temperature variation on a microbial fermentation process, which can be combined to modulate the metabolic activity of microorganisms during fermentation in order to improve the fermentative yields and productivities of the desired product. Highlights: Simultaneous variation of pressure and temperature affected the fermentative rate. Pressure effect depends on incubation temperature. Higher pressures and lower temperatures slowed down yogurt production. Fermentation at 10 MPa/43 °C improved fermentative yield and lactic acid efficiency. Pressure and temperature may be used to modulate microorganisms metabolism.